2011
DOI: 10.1091/mbc.e11-06-0585
|View full text |Cite
|
Sign up to set email alerts
|

The actin nucleation factor JMY is a negative regulator of neuritogenesis

Abstract: JMY is a p53 cofactor that was recently shown to nucleate actin assembly. Evidence is presented that the function of JMY in actin nucleation is regulated by an inhibitory activity in cells and that JMY has a previously unrecognized function as a modulator of neuritogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 61 publications
3
35
0
Order By: Relevance
“…Our data are similar to those reported in mice, with high levels of expression in the spleen and testis but lower levels in the lung, liver, kidney, and colon. The only discrepancy was human gastric mucosa, in which we found a higher level of JMY than was reported in the mouse [14]. Most positive tissues also expressed P53, consistent with the notion that JMY augments transcriptional activity [1] and suppresses cellular proliferation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our data are similar to those reported in mice, with high levels of expression in the spleen and testis but lower levels in the lung, liver, kidney, and colon. The only discrepancy was human gastric mucosa, in which we found a higher level of JMY than was reported in the mouse [14]. Most positive tissues also expressed P53, consistent with the notion that JMY augments transcriptional activity [1] and suppresses cellular proliferation.…”
Section: Discussionsupporting
confidence: 81%
“…By Western blotting, widespread expression in normal tissues has been reported in mice and in a small series of mammalian cell lines [14]. We raised and characterized a monoclonal antibody that detects JMY by Western blotting and in formalin-fixed paraffinembedded tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Spir proteins belong to a family of actin nucleators that includes Cordon-bleu (Cobl) and Junction-mediating and regulatory protein (JMY). Knockdown of Cobl reduced dendrite branching complexity in cultures of rat hippocampal neurons (Ahuja et al, 2007), and in Purkinje neurons in organotypic slices of mouse cerebellum (Haag et al, 2012), while JMY knockdown in mouse neuroblastoma cells enhanced neurite outgrowth (Firat-Karalar et al, 2011). Future experiments will determine whether and how Cobl, JMY and Spir proteins influence dendrite arborization in the mammalian brain.…”
Section: Discussionmentioning
confidence: 96%
“…Zuchero et al [12] and Firat-Karalar et al [26] demonstrated that purified JMY biochemically activates Arp2/3 ( Figure 5) induced actin polymerization in a dose dependent fashion. JMY does not induce elongation of preformed filaments but is able to nucleate new filaments, make them to elongate faster and cut filaments to make barbed ends.…”
Section: Jmy and Cell Motilitymentioning
confidence: 92%
“…The role played by JMY in actin regulation does not affect only the motility of the cell but, in the case of the neurons, it is also involved in the development of these cells as JMY inhibits the formation of neurites [26]. This inhibiting activity appears to be due to its function as an actin-assembly protein [26].…”
Section: Jmy and Cell Motilitymentioning
confidence: 99%